Efficient RNA isoform identification and quantification from RNA-Seq data with network flows. (9th May 2014) - Bernard, Elsa; Jacob, Laurent; Mairal, Julien; Vert, Jean-Philippe
Abstract : Motivation: Several state-of-the-art methods for isoform identification and quantification are based on ℓ 1 -regularized regression, such as the Lasso. However, explicitly listing the—possibly exponentially—large set of candidate transcripts is intractable for genes with many exons. For this reason, existing approaches using the ℓ 1 -penalty are either restricted to genes with few exons or only run the regression algorithm on a small set of preselected isoforms. Results: We introduce a new technique called FlipFlop, which can efficiently tackle the sparse estimation problem on the full set of candidate isoforms by using network flow optimization. Our technique removes the need of a preselection step, leading to better isoform identification while keeping a low computational cost. Experiments with synthetic and real RNA-Seq data confirm that our approach is more accurate than alternative methods and one of the fastest available. Availability and implementation: Source code is freely available as an R package from the Bioconductor Web site (http://www.bioconductor.org/ ), and more information is available at http://cbio.ensmp.fr/flipflop . Contact: Jean-Philippe.Vert@mines.org Supplementary information: Supplementary data are available at Bioinformatics online.